How can researchers facilitate the utilisation of research by policy-makers and practitioners in education?. Issue 4 (4th July 2019) - Ion, Georgeta; Stîngu, Mihaela; Marin, Elena
Abstract: Interest in research utilisation in policy and practice has grown in the last few years for both academics and users. This interest is partly due to changes in higher education institutions in many countries that emphasise a research-centred approach, which prioritises the dissemination and transfer of research results to end users. The process represents a paradigm shift and a challenge, especially for countries in which the transition from a university model based on teaching to one intensive in research is still ongoing. Our research analyses academics' perceptions in relation to the utilisation of their research in policy-making in Romania. One hundred and fifteen academics answered a survey based on an adapted research utilisation scale. Academics' perception is that educational research is generally only slightly used by policy-makers and practitioners. Academics have more influence on the transmission of knowledge and less on the rest of the research utilisation (RU) process, which involves end users. Furthermore, they generally see research as part of their professional growth and less as a way to respond to social problems.